2016
DOI: 10.1080/08869634.2016.1156282
|View full text |Cite
|
Sign up to set email alerts
|

Association of bone marrow edema with temporomandibular joint (TMJ) osteoarthritis and internal derangements

Abstract: Bone marrow edema, increased fluid level, and pain are associated with osteoarthritis in the majority of patients reporting TMJ arthritis. Degenerative and disc displacement conditions are multifactorial and require further investigations. Magnetic resonance imaging can be employed to detect bone marrow edema even in the absence of pain and clinical symptoms in the patients of internal derangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…TMD is a complex multifactorial condition that may be initiated by factors such as malocclusion, parafunctional habits (lip biting, bruxism) 31 and psychological factors, including anxiety or stress 31, 32, 33. Stress and parafunctional habits are well known factors that are associated with TMD symptoms in university students 15, 31.…”
Section: Discussionmentioning
confidence: 99%
“…TMD is a complex multifactorial condition that may be initiated by factors such as malocclusion, parafunctional habits (lip biting, bruxism) 31 and psychological factors, including anxiety or stress 31, 32, 33. Stress and parafunctional habits are well known factors that are associated with TMD symptoms in university students 15, 31.…”
Section: Discussionmentioning
confidence: 99%
“…A clear connection between joint effusion and osteoarthritis of the temporomandibular joint [16] and between joint effusion and disc displacement (particularly without repositioning in a functional position) was seen [17]. There was also a close connection between joint effusion and bone marrow edema in the capitulum in clinical pain syndrome [18]. A further MRI study in CMD patients (unsurprisingly) showed a clear statistical relationship between anterior disc dislocation seen on MRI, osteoarthritis, bone marrow edema, and joint effusion and a clinically manifested pain syndrome [19].…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, these data are in line with observations of human patients, who sometimes display such variability in synovial fluid volume. [33][34][35] Because FLSs are active players that contribute to cartilage damage in RA, we considered their potential role in the erosive process observed in the TMJ of K/BxN mice. We obtained and cultured primary FLSs from TMJs by using a protocol adapted from one that is usually used in our laboratory to harvest FLSs from limb joints.…”
Section: Discussionmentioning
confidence: 99%